Plasmonic Coupling in Three-Dimensional Au Nanoparticle Assemblies Fabricated by Anodic Aluminum Oxide Templates. (4th November 2013) - Sohn, Ahrum; Gwon, Minji; Choi, Dukhyun; Kim, Dong-Wook
Abstract : We investigated optical properties of three-dimensional (3D) assemblies of Au nanoparticles (NPs), which were fabricated by dewetting of thin Au layers on anodic aluminum oxides (AAO). The NP assembly had hexagonal array of repeated multiparticle structures, which consisted of six trimers on the AAO surface and one large NP in the AAO pore (pore-NP). We performed finite-difference time-domain simulation to explain the optical response of the NP assemblies and compared the calculation results with experimental data. Such complementary studies clearly revealed how the plasmonic coupling between the constituent NPs influenced the spectral response of our NP assemblies. In particular, comparison of the assemblies with and without pore-NPs suggested that strong plasmonic coupling between trimers and pore-NP significantly affected the spectra and the field distribution of the NP assemblies. Plasmonic multi-NP assemblies could provide us new platforms to realize novel optoelectronic devices.